Efektifitas Terapi Pijat Dalam Mengurangi Gejala Ispa Pada Anak - Selvia Sri Utami; Serly Marlina; Riska Silviana; Laili Rahmawati; Dwiyatun Dwiyatun; Liya Lugita Sari (Utami Publisher, 2026)
Acute respiratory infection (ARI) is an acute infectious disease that attacks a part of the respiratory tract, from the nose to the alveoli, caused by viruses and bacteria. Viruses and bacteria can spread through droplets and contaminated air environments. One thing that can be done to prevent ARI is to provide advice and training on the preparation of ginger honey drinks that contain antiseptics and antioxidants. These contents serve to reduce the severity of cough without causing side effects that can harm children's health. The purpose of the community service is to increase public awareness of ARI and provide training on the production of terphy massage The methods used in community service activities are in the form of counseling and training. The conclusion is that the public of Ponorogo village, RT 4, Lubuklinggau, has more knowledge about implementing complementary therapy massage for family members suffering from ARI. The community is encouraged to adopt clean and healthy lifestyle behaviors and diligently encourage children to wash their hands before and after eating